Hooked on screens: examining the motivational factors on binge-watching behaviour with attitude as a mediator - Chan, Tak Jie; Tengku Mohd Azzman, Tengku Siti Aisha; Darshini, Archana; Liew, Tze-Wei; Sharipudin, Mohamad Nor Sallehhudin (National University of Malaysia, 2026)
The emergence of various media service channels has caused the binge-watching phenomenon among viewers and brought adverse effects on media psychology. Various scholars have examined the Uses and Gratifications Theory (UGT) in understanding the motives of media consumption, but other motives require further examination. This study aims to examine the U&G motives (enjoyment, escapism, and social interaction) that influence the attitude and binge-watching behaviours through the extension of other motives (e.g., immersion and media appeal). The study applied quantitative research, with the use of purposive sampling to gather 280 valid responses via the online survey. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyse the data and test the hypotheses. The results corroborated that enjoyment, escapism, and media appeals were the predictors of binge-watching attitude, but social interaction and immersion were not. In addition, the attitude of binge-watching positively affects binge-watching behaviours. The study evidenced that attitude served as a mediator between the motives (enjoyment, escapism, media appeal) and binge-watching behaviour. This research contributed to the UGT and media scholarship, with evidence that media appeal (technological gratification) is a new motive. The findings of this study urge streaming services, media content producers, and governmental bodies to formulate media policies and digital literacy initiatives on binge-watching to avoid the negative media effects on the younger generations and society at large